2021
DOI: 10.1101/2021.02.05.21250672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in pregnancy – characteristics and outcomes of pregnant women admitted to hospital because of SARS-CoV-2 infection in the Nordic countries

Abstract: Introduction Population-based studies about the consequences of SARS-CoV-2 infection (COVID-19) in pregnancy are few and have limited generalizability to the Nordic population and health care systems. Material and method This study examines pregnant women with COVID-19 in the five Nordic countries. Pregnant women were included if they were admitted to hospital between March 1 and June 30, 2020 and had a positive SARS-CoV-2 PCR test 14 days or fewer prior to the admission. Cause of admission was classified a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
4
3
0
Order By: Relevance
“…As reported by other studies, [23][24][25][26][27][28] we confirmed that women who were obese and women with previous comorbidities were more likely to develop severe COVID-19 disease. Pregnant women from HMPCs were also significantly more likely to be hospitalised with severe pneumonia, probably because of their lower socio-economic status and possible through delays in accessing health services.…”
Section: Thorntonsupporting
confidence: 90%
See 2 more Smart Citations
“…As reported by other studies, [23][24][25][26][27][28] we confirmed that women who were obese and women with previous comorbidities were more likely to develop severe COVID-19 disease. Pregnant women from HMPCs were also significantly more likely to be hospitalised with severe pneumonia, probably because of their lower socio-economic status and possible through delays in accessing health services.…”
Section: Thorntonsupporting
confidence: 90%
“…Unexpectedly, we did not record a significant increase in the rate of CS, as reported in many systematic reviews, 27,29,30 and in the UK and Northern Europe, [23][24][25] where usually the CS rates are lower compared with Italy. The ItOSS detected a higher rate of CS only among women affected by COVID-19 pneumonia, whereas the increase reported by UKOSS is irrespective of symptom status.…”
Section: Thorntonsupporting
confidence: 48%
See 1 more Smart Citation
“…been shown that the risk of preterm birth and perinatal death may be increased in hospitalised pregnant women with COVID-19. 18 This was also found in a Nordic study that included data from Denmark, 19 but until October 2020, we have data that show that only a few pregnant women were admitted to Danish hospitals due to COVID-19. 20 Another study found that most of the preterm births in pregnant women with COVID-19 were iatrogenic.…”
Section: Discussionsupporting
confidence: 70%
“…Total score of GAD7 ranges from 0 to 21, higher scores indicate a higher level of generalized anxiety. The total score of GAD7 will be further categorized into severity categories of minimal (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21) anxiety. In this study, we used the Swedish version of GAD7 , which has demonstrated excellent internal consistency in previous studies.…”
Section: Generalized Anxiety Disorder-7 (Gad7)mentioning
confidence: 99%